Project Based Learning In PAI Subjects To Improve Student Collaboration And Creativity Skills - Qoidul Khoir (Journal on Education, 2024)
Project Based Learning has become an increasingly popular approach to improving students' skills in a variety of subjects. This research explores the implementation of Project Based Learning in Islamic Religious Education subjects to improve students' collaboration and creativity skills. The research method used was a classroom action study involving two classes of junior high school students as research subjects. During the research period, students are involved in projects based on PAI topics that are relevant to their daily lives. Data was collected through observation, interviews and analysis of student portfolios and carried out. The research results showed a significant increase in students' collaboration skills, such as the ability to work together in teams, effective communication, and conflict resolution. Apart from that, student creativity is also stimulated through project-centered learning, with innovative ideas and solutions generated in the context of PAI material. These findings confirm that Project Based Learning can be an effective approach in improving students' collaboration and creativity skills in the PAI learning context. The practical and pedagogical implications of these findings are discussed to support the development of curricula that are more student-oriented and relevant to current needs.